Reverse-engineering biological networks from large data sets - Natale, Joseph J.; Hofmann, David; Hernández Lahme, Damián Gabriel; Nemenman, Ilya (MIT Press, 2018)
Fil: Natale, Joseph J.. University of Emory; Estados Unidos